(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2011)
Studies have shown that winds have a great influence on military aviation flights in the area of Erebuni airport. So, during the cold period of the year, southern and South-West winds prevail and during the warm period – North-West. Annual average speed of southern, South-West and North-West winds are 5–8 m/s and gusts 25–28 m/s. During these winds flights are limited or stopped.